"VÔLEI MASCULINO É PRA HOMEM": REPRESENTAÇÕES DO HOMOSSEXUAL E DO TORCEDOR A PARTIR DE UM EPISÓDIO DE HOMOFOBIA - Luiza Aguiar dos Anjos (Universidade Federal do Rio Grande do Sul, 2015)
Based on an episode of homophobia that took place in a volleyball match, this paper examines representations of the categories of "homosexual" and "fan". Its sources were texts published about the case on websites of newspapers of nationwide circulation. Understanding representation as a product of meaning ascribed to things, we discuss the arguments used to construct the representations found - which are mostly guided by stereotypes of sports and the homosexualities that, regulated by power networks, are taken as naturally established truths.